Valor nutricional de alimentos alternativos para tambaqui (Colossoma macropomum) - SOARES, Karoline Julhice Araujo (2016)
The experiment was conducted in order to determine the chemical composition and digestibility coefficients (ADC) of dry matter (DM), crude protein (CP), ether extract (EE) and gross energy (GE) of alternative food plant for tambaqui (Colossoma macropomum). 108 tambaquis were used, with an average weight of 165.3 ± 15.6 g, with six treatments and three repetitions and six fish per experimental plot for 60 days. Fish were distributed in 18 cages shaped cylinder, which were in polythene containers with volume of 1000L each with individual aeration systems, supply and water drainage. In the period of collection of feces fish were kept during the day in polyethylene boxes, which were hand fed the will, and at 18: 00h the animals were transported to the stool collection tanks with 250L capacity and minimum water renewal 25 % per day using the modified Guelph system. Six experimental diets were made, with a reference, based on soybean meal and corn and the other containing 70% of the reference diet and 30% of foods tested (rice bran (FAI), hay flour of leucaena leaf ( FFL), cassava leaf hay flour (FFM), scrapes the full cassava root (RRIM) and babassu meal (TB). To evaluate the apparent digestibility of nutrients, we used the indirect method of feces collection by decantation and titanium dioxide as inert tracer added to the diet at a concentration of 0.1%. Apparent digestibility coefficients (ADCs) for MS, CP, EE and EB were 71.34%, 80.97%, 72.93% and 78.54% for FAI; 57.08%, 74.78%, 51.49% and 29.91% for FFL; 49.43%, 36.59%, 53.80% and 31.97% for FFM; 88.52%, 88.69%, 81.73% and 89.09% for RRIM and 38.29%, 29.16%, 37.60% and 25.68% for TB, respectively. Among the evaluated foods, rice bran and the scrapings of the full cassava root highlighted by high CADDM, CADCP, CADEE and CADGE, and lower NDF and ADF contents. Flour hay of leucaena leaf, cassava leaf hay flour and babassu meal had lower CADDM, CADCP, CADEE and CADGE and higher levels of NDF and ADF.